2019
DOI: 10.5513/jcea01/20.3.2223
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of lettuce (Lactuca sativa L.) and rainbow trout (Oncorhynchus mykiss W.) in the aquaponic recirculation system

Abstract: Aquaponics is combined growing fish and plants in a recalculating system. Therefore, it is very important to achieve optimal conditions for their cultivation. The purpose of this study was to trace the influence of the water used by the cultivated fish on the biomass of the lettuce in the aquaponic system. In this connection, two types of hydroponic sections were built and integrated into an existing recirculation aquaculture system. The hydrochemical parameters were measured during the trial. The duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Mineral wool and vermiculite were better substrates than perlite, coconut fiber, hydroleca, sphagnum moss, algae, and charcoal substrates in terms of spinach, chicory and basil production in aquaponic over the summer and autumn sessions (Khandaker and Kotzen, 2018;Nuwansi et al, 2016). A recent experiment found that lightweight expanded clay aggregate (LECA) as substrate yielded a higher lettuce product than the floating raft although the latter showed longer plant root (Velichkova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mineral wool and vermiculite were better substrates than perlite, coconut fiber, hydroleca, sphagnum moss, algae, and charcoal substrates in terms of spinach, chicory and basil production in aquaponic over the summer and autumn sessions (Khandaker and Kotzen, 2018;Nuwansi et al, 2016). A recent experiment found that lightweight expanded clay aggregate (LECA) as substrate yielded a higher lettuce product than the floating raft although the latter showed longer plant root (Velichkova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aquaponics can be integrated into raceway rainbow trout cultivation systems, enabling additional revenues (growing vegetables, insects) as well as improvements in wastewater quality [ 220 ]. The integration of the two aquaculture systems makes them largely non-consumer and non-polluting users of the water resources [ 221 ]. According to already performed experiments, rainbow trout in aquaponics is bred in round plastic or stainless-steel tanks [ 36 ].…”
Section: The Potential Of Rainbow Trout Farming In Aquaponicsmentioning
confidence: 99%
“…At the same time, revenues from the greenhouse also helped to compensate for the operating losses of the first year of the fish system. The economics of the fish system can be improved by increasing the scale of production [ 221 ] and by using fish species with great commercial value and high market prices, e.g., O. mykiss . However, the added technical complexity, marketing work, production and market risks, fish and plant diseases, mechanical failures, regulatory changes, and market fluctuations can significantly reduce projected returns [ 221 ].…”
Section: The Potential Of Rainbow Trout Farming In Aquaponicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lettuce (L. sativa L.) along with rainbow trout (Oncorhynchus mykiss w.) crops were grown within a recirculating aquaponic method. According to the study, the lightweight expanded clay aggregate section of a new aquaponics system removed more ammonium, nitrate, and orthophosphate than the raft portion of the plan (Velichkova et al 2019). Based on the study, the combination of water spinach plants with koi fish formed the maximum yield and determined the maximum complete development of fish and a survival rate of hundred percent (Andriani et al 2019).…”
Section: Lettuce and Water Spinach With Koi Fish And Rainbow Troutmentioning
confidence: 99%